Más allá de los límites del pensar discursivo. Notas sobre la figura del entendimiento intuitivo en la Crítica de la facultad de juzgar - Palermo, Sandra Viviana (2018)
The paper analyses the Kantian use of the notion of intuitive understanding as it appears in the third Critique. This analysis will highlight both problematic and fertility of this notion whose functions differ according to its systematic employment. In fact, according to the role that such understanding fulfills within the Kantian conceptual frame, it assumes different cognitive configurations, namely, (a) it shows that the principle of Zweckmäßigkeit is a valid transcendental presupposition only for our power of judgment, (b) it makes explicit that while purposiveness has just subjective validity, it is essential to understand specific natural beings; (c) it provides a model of synthetic totality which is accessible only trough the principle of purposiveness.